Legal Nature of Collective Labor Disputes - Nurmagambetov Amanzhol Magzumovich; Rakhimkulova Lola Ulugmurodovna (Genius Journals, 2023)
Conflict is inevitable in workplace relations. Establishing institutions and practices that are able to manage workplace conflict effectively is therefore an integral dimension of any workplace relations system. However, the nature of workplace relations and workplace conflict is changing. For example, as trade union density has declined, workrelated disputes have become increasingly individualised, rendering institutions built on the expectation of collective disputes struggling under the resulting workload
Keywords: collective; increasingly; resulting; built